‘Capitalness’ in the Mind of the Residents of Small Russian Towns: The Cases of Kasymov, Myshking and Old Ladoga - A. V. Salavatova (Сравнительная политика, 2015)
The term ‘capital’ is ambiguous. It means a certain geographical category, which has a sense in the context of various factors. A particular interest lays in the research of in small towns that have neither institutional structure nor any other prerequisites for naming themselves ‘capital’. However, their geographical image can be seen as the element of historic-cultural memory or as a touristic brand.